2023
DOI: 10.1146/annurev-fluid-120720-035029
|View full text |Cite
|
Sign up to set email alerts
|

The Flow Physics of Face Masks

Abstract: Although face masks have been used for over a century to provide protection against airborne pathogens and pollutants, close scrutiny of their effectiveness has peaked in the past two years in response to the COVID-19 pandemic. The simplicity of face masks belies the complexity of the physical phenomena that determine their effectiveness as a defense against airborne infections. This complexity is rooted in the fact that the effectiveness of face masks depends on the combined effects of respiratory aerodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 79 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…It should be noted that the permeability of the porous media also plays an important role. In fact, as the porosity of the mask filter decreases, its permeability decreases, and the pressure drop increases [34].…”
Section: Darcy's Lawmentioning
confidence: 99%
“…It should be noted that the permeability of the porous media also plays an important role. In fact, as the porosity of the mask filter decreases, its permeability decreases, and the pressure drop increases [34].…”
Section: Darcy's Lawmentioning
confidence: 99%
“…Permeability results are available for mask materials, largely coming out of the textile industry [6]. A recent review of the fluid dynamics-centric materials can be found in the work of Rajat et al [8]. The work presented in the current paper involves flow through a compressible filter which was studied by Köry et al [5] in the context of industrial filtering.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work Face masks have been used for centuries to provide protection from pollutants and pathogens, but attempts to understand the physics of the flow and the filtration physics in this context are more recent, with an enormous increase in activity since the advent of the COVID-19 pandemic. The associated fluid dynamics is complicated involving, as it does, scales varying from nanometres (fibre diameter) to metres (the distance travelled by a respiratory jet), with structural dynamics, droplet and particle dynamics, and even electrostatics playing a role [8]. Computational mask flow experiments have been undertaken using real world observations [1].…”
Section: Introductionmentioning
confidence: 99%